Cicero and the US Political Culture of the 18th–19th Centuries - Процюк, А. (Київський національний університет імені Тараса Шевченка, 2018)
This article covers the role of Ancient Roman statesman and intellectual Marcus Tullius Cicero in the culture of the United States of America during the 18th and 19th centuries, particularly his influence on the formation of democracy in the US. While the recent decades have witnessed the increasing scholarly attention to the impact of Cicero on the early political culture of the US, the body of historical research, especially the Ukrainian one, lacks general analyses of Cicero's role in the American political system during the emergence of the American state and its existence on the early stages of its history. After a general overview of the historical context of Cicero's biography and legacy, this article pays a particular attention to his impact on the creation of United States democracy. A significant number of Cicero's ideas, more or less, had been reflected in the concepts which defined the newly created American democracy. The most important concepts in this regard are the ideas of a republic government, private property, just laws, and forms of state structure. Apart from the general importance of Cicero's ideas for the early American democracy, Marcus Tullius Cicero himself was a notable example for some Founding Fathers of the US, especially for the 2nd President John Adams. During the 19th century, Cicero continued to play a significant role in the American society, specially in the fields of education and public speaking.

Розглядається роль давньоримського державного діяча та інтелектуала Марка Туллія Цицерона в культурі Сполучених Штатів Америки XVIII-XIX ст., зокрема його вплив на формування демократії США. Хоча протягом останніх десятиліть американські науковці звертають все більшу увагу на вплив Цицерона на ранню політичну культуру США, в історіографії – а тим більше в українській історіографії – не вистачає загального аналізу ролі Цицерона в американській політичній системі протягом зародження Американської держави та її існування на ранніх етапах її історії. Після загального огляду історичного контексту біографії та спадку Цицерона, у статті звертається особлива увага на його вплив на створення демократії Сполучених Штатів. Значна частина ідей Цицерона тією чи іншою мірою відбилася в концепціях, на яких базувалася новостворена американська демократія – йдеться в першу чергу про ідеї щодо республіканського устрою, приватної власності, справедливого законодавства і форми державного устрою. Окрім загальної важливості ідей Цицерона для ранньої американської демократії, особа Цицерона була прикладом для деяких Батьків-засновників США, особливо для Джона Адамса, другого президента США. Протягом XIX ст. роль Цицерона в американській культурі продовжувала бути значною; зокрема це особливо проявлялося у сферах освіти та ораторського мистецтва.
Цицерон та політична культура США XVIII-XIX століть
Keywords: Marcus Tullius Cicero; early US history; American culture; Founding Fathers of the US; US democracy; Марк Туллій Цицерон; рання історія США; американська культура; Батьки-засновники США; демократія США